Mid-Late Holocene Stalagmite δ18O and δ13C Records in Naduo Cave, Guizhou Province, China - Jialu Wang (Journal of Chemistry)
Global warming and climate anomalies have attracted worldwide attention. The study of global climate change has received increasing attention from all countries and fields worldwide. Paleoclimate research is an important way to understand past global change and environmental evolution and to simulate and predict future climate development. A stalagmite ND3 collected in Naduo Cave was used to reconstruct the history of local climate and environmental changes from 0.55 to 5.07 ka BP based on the data of 13 230Th ages and 642 groups of oxygen and carbon stable isotopes. First, according to correlation analysis, δ18O and δ13C were significantly correlated (correlation coefficient r = 0.308, n = 318, P<0.001) during the 5.07–2.00 ka BP period. However, during the period of 2–0.55 ka BP, there was no significant correlation P>0.05. The δ18O and δ13C data indicate that the climatic environment changed asynchronously during the period of 2.00–0.55 ka BP. During the period of 5.07–2.00 ka BP, the influence of human activities was weak, and δ18O and δ13C indicate similar climatic and environmental conditions, both of which changed in the same direction (positive correlation). In other words, when δ18O was positive, it indicated weak summer monsoons and lower precipitation, which led to declines in vegetation, weakened biological activity, and decreased soil CO2 and positive δ13C. The reverse patterns were also true. Since 2.0 ka BP, the intensity of human activities and the transformation and influence of surface vegetation have increased, and native vegetation has been destroyed in large quantities. Therefore, the climatic and environmental significance indicated by δ13C and δ18O has been well demonstrated. Second, the δ18O records showed that stalagmite ND3 responded to the weak monsoon drought events of 4.2 ka BP and 2.8 ka BP in the Holocene in a discontinuous deposition manner, which brings up new directions for future research.